MAIN DIRECTIONS OF SMART AGRICULTURE PROBLEMS AND SOLUTIONS - Noraliyev N. X. (European Science Publishing, 2024)
This article examines the main directions of smart agriculture and the problems faced by modern farmers. The author discusses the benefits of using the latest technologies and innovations in agriculture and offers practical solutions to improve production efficiency and reduce costs. The article discusses such areas of smart agriculture as digitalization of production, automation and robotization, the use of sensors and the Internet of things, as well as the use of artificial intelligence and data analytics. The author also discusses the problems associated with the lack of qualified personnel, the high costs of introducing new technologies and the difficulties in processing and analyzing large volumes of data. Overall, the article provides a useful overview of the main trends in smart agriculture and offers practical recommendations for improving productivity and competitiveness in the field.
Keywords: smart agriculture, IoTe, digital devices, artificial intelligence, machine learning, big data, automation, remote sensing, energy efficiency, resource management, digitalization, innovation.